Sulphasalazine induced renal failure. - Dwarakanath, A D (1992)
Two men with longstanding ulcerative colitis who were treated with sulphasalazine for several years and who developed chronic renal failure are reported. Renal biopsy specimens showed histological changes consistent with drug induced chronic intestinal nephritis. Extensive investigation made other causes of chronic renal failure unlikely. One of these patients underwent renal transplantation, the other has impaired but stable renal function.